HIV INFECTION, ANTIRETROVIRAL THERAPY AND CARDIOVASCULAR RISK - Katleen de Gaetano Donati; Roberto Cauda; Licia Iacoviello (Mediterranean Journal of Hematology and Infectious Diseases)
In the last 15 years, highly active antiretroviral therapy (HAART) has determined a dramatic reduction of both morbidity and mortality in human immunodeficiency virus (HIV)-infected subjects, transforming this infection in a chronic and manageable disease. Patients surviving with HIV in the developed world, in larger number men,  are becoming aged. As it would be expected for a population of comparable age, many HIV-infected individuals report a family history of cardiovascular disease, a small proportion have already experienced a cardiovascular event and an increasing proportion has diabetes mellitus. Smoking rate is very high while an increasing proportion of HIV-infected individuals have dyslipidaemia. Studies suggest that these traditional risk factors could play an important  role in the development of cardiovascular disease in these patients as they do in the general population. Thus, whilst the predicted 10-year cardiovascular disease risk remains relatively low at present, it will likely increase in relation to the progressive aging of  this patient population. Thus, the long-term follow-up of HIV infected patients has to include co-morbidity management such as cardiovascular disease prevention and treatment. Two intriguing aspects related to the cardiovascular risk in patients with HIV infection are the matter of current investigation: 1) while these subjects share many cardiovascular risk factors with the general population, HIV infection itself increases cardiovascular risk; 2) some HAART regimens too influence atherosclerotic profile, partly due to lipid changes. Although the mechanisms involved in the development of cardiovascular complications in HIV-infected patients remain to be fully elucidated, treatment guidelines recommending interventions to prevent cardiovascular disease in these individuals are already available; however, their application is still limited.